Exonephology: transmission spectra from a 3D simulated cloudy atmosphere of HD 209458b. Issue 1 (23rd August 2018) - Lines, S; Manners, J; Mayne, N J; Goyal, J; Carter, A L; Boutle, I A; Lee, Elspeth; Helling, Ch; Drummond, B; Acreman, D M; Sing, D K
ABSTRACT: We present high-resolution transmission spectra, calculated directly from a 3D radiative hydrodynamic simulation that includes kinetic cloud formation, for HD 209458b. We find that the high opacity of our vertically extensive cloud deck, composed of a large number density of sub-μ m particles, flattens the transmission spectrum and obscures spectral features identified in the observed data. We use the pandexo simulator to explore features of our HD 209458b spectrum which may be detectable with the James Webb Space Telescope . We determine that an 8–12μ m absorption feature attributed to the mixed-composition, predominantly silicate cloud particles is a viable marker for the presence of cloud. Further calculations explore, and trends are identified with, variations in cloud opacity, composition heterogeneity, and artificially scaled gravitational settling on the transmission spectrum. Principally, by varying the upper extent of our cloud decks, rainout is identified to be a key process for the dynamical atmospheres of hot Jupiters and shown to dramatically alter the resulting spectrum. Our synthetic transmission spectra, obtained from the most complete, forward atmosphere simulations to date, allow us to explore the model's ability to conform with observations. Such comparisons can provide insight into the physical processes either missing or requiring improvement.